Analysis of carotene content in CPO to assess the quality of RBD palm olein (cooking oil) - Lestari, Puji; Silalahi, Yosy Cinthya Eriwaty; Yusuf, Faisal (Science Midwifery, 2025)
Fresh fruit bunches (FFBs) from oil palms serve as the primary raw material for crude palm oil (CPO) production. Among various quality parameters, the Deterioration of Bleachability Index (DOBI) and carotenoid content—particularly β-carotene—are critical indicators of CPO quality. A higher DOBI value generally reflects a lower concentration of oxidized carotenes, which facilitates the bleaching process, as the color imparted by oxidized carotenoids is more difficult to remove through conventional heating. The samples are CPO were randomly collected from production facilities located in North Sumatra. Range DOBI is 2.27 – 2.66 and range carotene 401 – 492 ppm. Average DOBI is 2.44 is showing that the quality of CPO is fair and can be used to processed as cooking oil.